Exponering av trägolv och lister i butik och på mässor : en jämförande studie mellan sport- och bygghandeln - Persson, Fredrik (SLU/Dept. of Forest Products, 2007)
The business cycle of the wood flooring branch is currently high however that situation may not be sustainable. In a possible future weaker business climate, the importance of marketing becomes accentuated for firms that aim to maintain their sales levels. We can see trends that competition among the Swedish and foreign manufactures is already stepping up.